Catalytic cracking of vacuum gas oil over the modified mordenites and Y-type zeolites mixed with alumina - Lee, KH; Ha, BH; Lee, YW (AMER CHEMICAL SOC, 1998)
Catalytic cracking of vacuum gas oil has been studied over pure zeolites modified by steaming and acid treatment, and zeolite/alumina catalysts containing any of the former zeolite (35 wt %) and alumina (65 wt %) with a different pore size distribution. The conversion of vacuum gas oil (VGO) over zeolite/alumina catalysts with a wide pore size distribution is almost the same as that over pure zeolites, but less coke is formed over zeolite/alumina compared to that over pure zeolites. The catalysts containing zeolite Y show higher conversion of VGO than on the catalysts containing mordenite. In addition, the catalysts containing modified mordenite, resulting in the development of mesopores, have improved activity and selectivity for gasoline compared to those containing mordenite with a micropore structure. Selectivity of olefin is higher on the catalysts containing mordenites compared to the catalysts containing zeolite Y because of low-bimolecular hydrogen-transfer reaction rates. The distribution of paraffin and olefin in gasoline products does not depend on the addition of alumina in mixed catalysts but rely on mainly the zeolite type. The influence of shape selectivity on products distribution causes the catalysts containing zeolite Y with large kinetic diameter to produce more branched aromatics than those containing mordenites. The modified mordenite catalysts having mesopores in the 4-nm range yield more aromatics compared to the catalysts containing mordenite with mostly micropore. Catalysts containing zeolite Y give the highest yield of xylene whereas the catalysts containing mordenites produce a maximum yield of toluene.
Keywords: NI-MO/AL2O3 CATALYSTS; PORE STRUCTURE; USY; HYDROCRACKING; MCM-41